Technology Acceptance, Perceived Risk, and QRIS Purchase Intention: A Gender Comparison Among Generation Z College Students - Anggie Eka Wardani; Yogi Dwi Satrio; Wahjoedi Wahjoedi; Bagus Shandy Narmaditya (Jurnal Inovasi Pendidikan Ekonomi, 2026)
This research investigated the influence of technology acceptance and perceived risk on purchase intention toward QRIS and investigated the possible difference between genders among undergraduate students. A quantitative approach was used with data collected from 374 respondents through an online questionnaire. Respondents were obtained by multistage sampling and the data was analyzed by multiple linear regression and independent-samples t-test using IBM SPSS Statistics version 25. The analysis showed that technology acceptance has a positive and significant effect on purchase intention. whereas perceived risk showed a significant but comparatively weaker negative relationship. Collectively, the two variables explained a substantial proportion of the variation in purchase intention. In addition, no significant gender differences were identified in technology acceptance, perceived risk, or purchase intention. The overall findings suggested that male and female students in Generation Z responded to QRIS in remarkably similar ways, reflecting an increasingly gender-neutral pattern of digital payment adoption.